Intelligent Test Design Based on AC-drive Test Platform - JI Zhiyuan; CHENG Hao; LIU Hulin; GAO Liansheng (机车电传动)
The intelligent test design was introduced from principle, communication mode and program structure, which could automatically analyze the test outline, generate the operation logic of the test equipment, process the original data and generate the report. The advantages of the design were verified by the torque characteristic test and the traction power supply voltage interruption test, which were the typical test of IEC 61377-3:2002.The design improved the intelligence level of the test.